Edukasi Penggunaan Terapi Komplementer untuk Mengatasi Dismenorea Primer di SMAN 7 Kota Jambi - Safitri, Safitri; Hayati, Fatihatul; Maharani, Sri (Jurnal Abdimas Kesehatan (JAK), 2025)
Adolescence is a period of secondary physical and sexual growth changes, one of which is menstruation. The prevalence of menstrual pain in Indonesia reaches 98.8% in teenagers. Menstrual pain has a direct effect that negatively impacts the quality of life of teenagers, such as interfering with daily physical activity, school attendance, study concentration and even academic achievement. Complementary therapy has been used by 15.5-79.3% and has been proven to be effective in treating primary dysmenorrhoea, including complementary therapy with warm water compresses, herbs, drinking mineral water and relaxation. SMAN 7 Jambi City is located in Danau Teluk District, the working area of the Olak Kemang Community Health Center which is often used as a place for health education. Preliminary studies conducted show that youth posyandu have been formed and are being implemented every month. However, not many teenagers attend, so to overcome this, health education is carried out in schools. Apart from that, the results of interviews with PMR teachers showed that at SMAN 7 Jambi City they had never received education from health workers regarding the use of complementary therapies to treat primary dysmenorrhoea. This activity aims to provide education about the use of complementary therapies to treat primary dysmenorrhoea. Carried out on 22 young women in class XII F1 at SMAN 7 Jambi City from September 2023 to February 2024. The expected target is to increase knowledge between before and after being given education. The method used is education using leaflets. Knowledge is assessed through the results of filling out a questionnaire. Monitoring and evaluating activities using a one group pretest and posttest design approach. The results of the service showed an increase in knowledge after being given education on the use of complementary therapies to overcome dysmenorrhea by 59%, so that young women can use complementary therapies to overcome dysmenorrhea independently.